Multi-omics approach to study the dual effects of novel proteins on the intestinal health of juvenile largemouth bass (Micropterus salmoides) under an alternate feeding strategy - Li, Lukuan; Wang, Yu; Huang, Yanqing; Wang, Chunfang (Frontiers in Immunology, 2023)
In an effort to minimize the usage of fishmeal in aquaculture, novel protein diets, including Tenebrio molitor, cottonseed protein concentrate, Clostridium autoethanogenum, and Chlorella vulgaris were evaluated for their potential to replace fishmeal. Nevertheless, comprehensive examinations on the gut health of fish under an alternate feeding strategy when fed novel proteins are vacant. Five isonitrogenous and isolipidic diets containing various proteins were manufactured, with a diet consisting of whole fishmeal serving as the control and diets containing novel proteins serving as the experimental diets. Micropterus salmoides with an initial body weight of 4.73±0.04g employed as an experimental animal and given these five diets for the first 29 days followed by a fishmeal diet for the next 29 days. The results of this study demonstrated that the growth performance of novel protein diets in the second stage was better than in the first stage, although only the Chlorella vulgaris diet increased antioxidant capacity and the cottonseed protein concentrate diet decreased it. Concerning the intestinal barriers, the Clostridium autoethanogenum diet lowered intestinal permeability and plasma IL-1β/TNF-α. Additionally, the contents of intestinal immunological factors, namely LYS and sIgA, were greater in Chlorella vulgaris than in fishmeal. From the data analysis of microbiome and metabolome, the levels of short chain fatty acids, anaerobic bacteria, Lactococcus, and Firmicutes were significantly higher in the Clostridium autoethanogenum diet than in the whole fishmeal diet, while the abundance of Pseudomonas, aerobic bacteria, Streptococcus, and Proteobacteria was lowest. However, no extremely large differences in microbiota or short chain fatty acids were observed between the other novel proteins and the whole fishmeal. In addition, the microbiota were strongly connected with intestinal short chain fatty acids, lipase activity, and tight junctions, as shown by the Mantel test and Pearson's correlation. Taken together, according to Z-score, the ranking of advantageous functions among these protein diets was Clostridium autoethanogenum diet > Chlorella vulgaris diet > whole fishmeal diet > cottonseed protein concentrate > Tenebrio molitor diet. This study provides comprehensive data illustrating a mixed blessing effect of novel protein diets on the gut health of juvenile largemouth bass under an alternate feeding strategy.